Diseño de un manual de ejercicios lúdicos que permitan el desarrollo de la coordinación psicomotriz en los niños de la Unidad Educativa Sierra Flor de la Parroquia Mulaló en el año lectivo 2012 – 2013 - Díaz Toapanta, Marco Francisco (2013)
This present paper is aimed to analyze the difficulties of psychomotor coordination in the children through different stages of the psychomotor development. The problem relates to the lack of application of lúdicas activities that help to the adequate development of psychomotor coordination nonexistent in several children. This work provides activities according to the different factors involved in the psychomotor development basing in theoretical, philosophical and psychological aspects that support this research. In this work was applied descriptive and the field investigation with these kind of research I could conclude that there is not the application of specific activities of the ludico aspect to allow an optimal psychomotor development in the children. For this reason, it was necessary to elaborate a manual of lúdicos exercises that help the increase of these abilities. This manual is a valuable tool that facilitates the labor of the early childhood educator in order to improve the handling in the psychomotor area in base to adapted activities to the different stages of the child development from the 2 years old in the Educative Centre “Sierra Flor”.